Respirar como direito de existir: epistemologia do armário e trajetórias de vida de mulheres lésbicas - Moraes, Simone Silveira (2024)
The research aimed to analyze the life trajectories of lesbian women, focusing on the experiences of refuges and coming out of the closet in the context of their relationships with other women in the family and how these interactions can affect mental health, especially with regard to anxiety. Using a qualitative approach and semi-structured interviews, three women who self-identify as lesbians, living in the interior of the State of São Paulo, aged between 35 and 48, were interviewed. The speeches of these women were analyzed based on the theoretical-methodological discursive practices of social psychology. The results revealed that lesbian women face high levels of anxiety due to the heteronormative prejudice still prevalent in society. Another aspect identified was that the impact of social class and race on the experiences of these women, found in the analysis of the intersectionality of sexual orientation, class and race, further aggravates the prejudice and discrimination experienced. Black lesbian women face the accumulation of the color marker in their struggles and financial vulnerability affects lesbian women even more, especially in the face of family discrimination, when it can force them to leave home. Thus, the analysis of the interviews identified that interactions with family members, especially with women in the family, can be both sources of support and stress, significantly influencing the mental health of the interviewees, revealing that family acceptance or rejection affects anxiety levels of lesbian women. The research also revealed the role of religion in the lives of the interviewees and how religious backgrounds can contribute to increased levels of anxiety, as well as establishing themselves as a source of well-being and belonging. The study revealed that lesbian women can face great difficulty breathing when they come out of the closet, as the looks of family members who could welcome them often fail to recognize their identity.